Phenylalanine derived Zwitterion as novel Corrosion Inhibitor for Mild Steel in 1M HCl: Electrochemical, Surface and DFT studies - Haque J.; Srivastava V.; Quraishi M.A. (My University, 2025)
The Phenylalanine based corrosion inhibitor 2-(3-(1-carboxy-2-phenylethyl)-1H-imidazol-3-ium-1-yl)-5-methyl-3-phenylpropanoate (IP) was synthesized by the condensation of phenylalanine, 2-oxopropanal, and formaldehyde and characterized by the FTIR and NMR spectroscopy. The corrosion inhibition performance of synthesized inhibitor was studied by electrochemical impedance spectroscopy (EIS), potentiodynamic polarization (PDP), Surface and DFT methods. The results show the studied IP is an effective inhibitor which showed the maximum inhibition efficiency of 96.08% at concentration 200ppm. The results of PDP study revealed that IP act as mixed type inhibitor. The results of EIS studies showed that IP inhibits the mild steel corrosion through the adsorption mechanism. The adsorption of synthesized phenylalanine derived Zwitterion on the mild steel surface was followed the Langmuir adsorption isotherm. The formation of inhibitor film on mild steel surface was confirmed by the scanning electron microscope (SEM) and energy-dispersive X-ray spectroscopy (EDX). The quantum chemical parameters were used to study the reactivity of IP inhibitor with iron surface. An inhibitor adsorption model is proposed. © 2019 by NACE International.